Chronic kidney disease among US adults with type 2 diabetes and cardiovascular diseases: A national estimate of prevalence by KDIGO 2012 classification. Issue 1 (January 2019) - Wang, Tongtong; Xi, Yuzhi; Lubwama, Robert; Hannanchi, Hakima; Iglay, Kristy; Koro, Carol
Abstract: Aim: Data on prevalence of chronic kidney disease (CKD) among US adults with type 2 diabetes (T2D) and cardiovascular diseases (CVD) are limited. The aim of this study was to provide such estimates for T2D, both overall and in those with CVD. Materials and methods: Using the NHANES 2007–2014 data, we conducted a cross-sectional analysis of an adult sample with diagnosed and undiagnosed T2D, aged ≥18 years. CVD was defined based on self-reported personal interview data on a broad range of health conditions—congestive heart failure, coronary heart disease, angina, stroke, or heart attack. T2D was defined as diagnosed T2D (self-reported provider diagnosis) and undiagnosed T2D (FPG ≥126 mg/dL or HbA1c ≥ 6.5% without self-reported diagnosis). Participants who started insulin within a year of T2D diagnosis, or were pregnant at the time of health examination were excluded. Appropriate sample weights were used to provide a national estimate. Results: The prevalence of moderate to severe renal impairment based on eGFR below 60 ml/min/1.73 m 2 among T2D was 18.0%. The prevalence of mild renal impairment was 36.9%: 28.3% with UACR<30 mg/g, 7.0% with UACR ≥30–300 mg/g and 1.6% with UACR >300 mg/g. For T2D and CVD subgroup, the prevalence was 33.6% for moderate to severe renal impairment and 42.8% for mild renal impairment. Conclusions: This study confirms the high prevalence of CKD in patients with multiple comorbidities: T2D and CVD. It also provides estimates of the prevalence of CKD categories based on KDIGO 2012 classification for US adults with T2D.